Cultural Identity of Pesantren Cadres in Indonesia - Nidzom, Muhammad Faqih; Saifuddin, Ahmad Farid; Khakim, Usmanul; Cahyo, Eko Nur (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2024)
This study aims to explore the cultural identity of pesantren cadres through the rite of self-endowment (waqf basyari) at Pondok Modern Darussalam Gontor (PMDG). The research employs a qualitative field methodology with an ethnographic approach. Data were collected through participant observation, in-depth interviews with eight informants (two pesantren leaders, four senior cadres, and two junior cadres), and documentation. Data analysis followed Spradley’s ethnographic method, including identifying social domains, semantic relationship analysis, taxonomic analysis, componential analysis, and the identification of cultural themes. The findings reveal that the wakaf diri ritual at PMDG comprises three phases of a rite of passage: separation, liminality, and incorporation. Upon completing these phases, cadres gain a new status as wakaf cadres with a cultural identity encompassing symbolic and intrinsic dimensions. The symbolic identity includes the cadres' daily roles in educating students, assisting the pesantren, and pursuing studies, balanced by entitlements such as welfare as members of the pesantren community. The intrinsic identity consists of three core dimensions: (1) achievements in academic and non-academic fields, (2) dedication through the sacrifice of time, effort, thoughts, and even life, and (3) loyalty manifested as a commitment to PMDG's values, leadership, and system. The intrinsic identity reflects self-development, dedication, and profound love for the pesantren. This ritual shapes cadres who are loyal and uphold the values of the pesantren in their lives.